Desenvolvimento de ferramenta digital para localizar aulas na UFERSA Campus Caraúbas-RN - Carmo Júnior, Francisco Augusto Alves do (Universidade Federal Rural do Semi-Árido, 2018)
With the advancement of technology, more applications and tools are incorporated into mobile platforms. From this context comes the opportunity to explore topics on the development of digital tools, focusing on the Android platform.This work aims to apply the results of the basic research using the Java language adopted by the platform in question, familiarization with the development tools, research on the services offered by Google for developers, the use of Google Maps, Google Direction API, Firebase database and Android Studio.Based on the above, it was possible to construct the prototype of an application that allows students to draw routes to their classrooms, facilitating the integration of new students to UFERSA Campus Caraúbas - RN.
Monografia
Keywords: Tecnologia; API; Geolocalização; Rotas; Aplicativo; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA